قواعد النظر في دلالات الألفاظ عند المالكية -  يسرى توماتية;  خيرة أسماء كريدة; د. علالي امحمد (جامعة عمار ثليجي الاغواط, 2023)
تهدف هذه الدراسة إلى إبراز بعض القواعد الأصولية التي تنظر في دلالات الالفاظ عند المالكية والتي بواسطتها يتم استخراج الأحكام الشرعية من الأدلة الخاصة بها. تعرضنا إلى مفاهيم عامة لكل جوانب الموضوع وقمنا بتعريف القواعد الأصولية وأهميتها مع إبراز الفرق بينها وبين القواعد اللغوية ثم عرفنا النظر مع بيان أقسامه. وفي الجانب التطبيقي بينا ماهية دلالات الألفاظ مع أقسامها، بعدها أبرزنا بعض قواعد النظر في دلالات الالفاظ عند المالكية مع الدليل. وإبراز هذه القواعد يمنح إضافة لعلم أصول الفقه وكذا تنوعا في الد راسة ويفتح ابوابا جديدة للاجتهاد. الكلمات المفتاحية: الدلالات الألفاظ القواعد المالكية. – - - Abstract:Abstract: Abstract: This study amis highlight somme of the fundamentalist rules that look at the semantics of the words of the Malikis, and by means of which the legal rulings are extracted from their own evidence. So that we presented general concepts for all aspects of the subject, and we defined the fundamentalist rules and their importance, while highlighting the difference between them and the linguistic rules. Then we knew looking with its statement and its divisions. On the applied side, we explained what the semantics of words are with their divisions, then we highlighted some rules for considering the semantics of words according to the Malikis with the evidence. Highlighting these rules gives an addition to the science of jurisprudence, as well as diversity in the study and opens new doors for diligence. key words: Semantics - Pronunciation - Grammar - Maliki